2013
DOI: 10.1088/0953-2048/26/9/095002
|View full text |Cite
|
Sign up to set email alerts
|

First-principles calculations of niobium hydride formation in superconducting radio-frequency cavities

Abstract: Abstract. Niobium hydride is suspected to be a major contributor to degradation of the quality factor of niobium superconducting radio-frequency (SRF) cavities. In this study, we connect the fundamental properties of hydrogen in niobium to SRF cavity performance and processing. We modeled several of the niobium hydride phases relevant to SRF cavities and present their thermodynamic, electronic, and geometric properties determined from calculations based on density-functional theory. We find that the absorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 83 publications
2
25
0
Order By: Relevance
“…First-principle calculations of Nb hydride formation showed that a single vacancy can accommodate six hydrogen atoms in the symmetrically equivalent lowest-energy sites and additional hydrogen in the nearby interstitial sites affected by the strain field. This indicates that a vacancy can serve as a nucleation center for hydride phase formation [19]. The trapping in vacancies was experimentally confirmed by positron annihilation experiments [28] where four hydrogen atoms were detected in one vacancy.…”
Section: Introduction: Hydrogen Absorption In Metals-bulk Versus Thinmentioning
confidence: 85%
See 2 more Smart Citations
“…First-principle calculations of Nb hydride formation showed that a single vacancy can accommodate six hydrogen atoms in the symmetrically equivalent lowest-energy sites and additional hydrogen in the nearby interstitial sites affected by the strain field. This indicates that a vacancy can serve as a nucleation center for hydride phase formation [19]. The trapping in vacancies was experimentally confirmed by positron annihilation experiments [28] where four hydrogen atoms were detected in one vacancy.…”
Section: Introduction: Hydrogen Absorption In Metals-bulk Versus Thinmentioning
confidence: 85%
“…An example is Nb-based superconducting radio-frequency cavities of particle accelerators, where metal-hydride surface layers can develop, leading to undesirable extra surface resistivity [19]. For a theoretical understanding of the remarkable changes of thin-film properties due to hydrogen charging, it is important to know how hydrogen is incorporated into the films, whether thermodynamic phase diagrams of the corresponding bulk materials are applicable, and how hydrogen absorption and its kinetics depend on various external parameters such as temperature and hydrogen pressure.…”
Section: Introduction: Hydrogen Absorption In Metals-bulk Versus Thinmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the underlying mechanisms for this effect are also not well understood, although a number of models have been proposed [17]. Recent studies suggest connections to the oxygen and hydrogen concentrations, and niobium vacancies, which we have shown to nucleate hydride precipitates in a recent density functional theory study [23]. However, a single model that explains all these effects does not exist.…”
Section: Introductionmentioning
confidence: 91%
“…Note that some of the hydrogen can also be trapped by vacancies. Two situations may occur: in a single vacancy up to six H atoms can be trapped, and there are evidences that more H tends to gather in the vicinity, providing nucleation sites for hydrides [121]. In the presence of interstitials atoms like O, N, C, those atoms will occupy preferentially the vacancy: each oxygen, nitrogen or carbon impurity traps only a single hydrogen atom under formation of oxygen-hydrogen, nitrogen-hydrogen or carbon-hydrogen pairs, where the trapped hydrogen occupies interstitial trap sites in the neighborhood of the trapping impurity [122][123][124][125].…”
Section: A Segregation Due To Crystalline Defectsmentioning
confidence: 99%